Construire un autre regard sur l’abandon, réactiver la charge de potentialités du projet - Tiphaine Abenia (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
How does an abandoned structure relate to the notion of failure ? What happens to the project once its abandonment is acted ? Based on a research work carried out on a large corpus of abandoned buildings, this article follows the trajectory drawn in time by these structures in order to study the crossing between two couples : project/construction on one hand and failure/potential on the other hand. First, the contribution replaces abandonment as a dismissed life cycle moment, weakly addressed by design mechanisms. By positioning abandonment as a moment of change between successive periods of different dynamics and by studying the conditions of its appearance as well as the underlying causes of its development, it draws fundamental distinctions between abandonment and failure of the project. If failure marks a final point, resulting from convergence, the abandonment oscillates between resistance and potential in a divergent movement. The article explores, in a final part, the capacity of abandonment to open up the field of potentialities associated with the project (from the scenarios that it keeps active to the tectonic ambiguity that it nourishes). The article thus lays the foundations for a non-linear reading of the biography of contemporary built situations.